'Of course we record it': legacy, textual violence, and fridging in Ales Kot's Zero. Issue 3 (4th May 2017) - Hong, Tiffany
ABSTRACT: Ales Kot's Image title Zero interrogates the refusal of the depiction of sexual violence, the trope of fridging as a metacritique of artistic inspiration, and the literalisation of dehumanising language as a commentary on barren cycles of masculinist violence and the narration of that violence. The function of sexual profanity that dissociates itself from reproductive or generative meaning is here reduced to referencing impotent, corporeal acts that the work consistently frames within male anxieties of conquest, virility, lineage and mortality. The latter arcs interrogate the gendered linguistic violence inherent in and essential to male narrative production. Lastly, the series conflates historical and fictional exclusion of the female, incorporating William S. Burroughs as Zero 's 'author' in an imaginary life palimpsest of literary and literal father–son narratives. Specifically, Burroughs' confession to his wife's death as vital in the development of his art is taken as Zero 's source for a metacommentary on fridging not as a hermetic and technical literary device, but rather its counterpart in reality: that is, male narrative as privileged and prioritised, normalised and historicised as rightfully reliant on the (self-)sacrificial and often violent erasure of the female. Zero consistently destabilises an originary point of epistemological and narrative, let alone chronological, authority, and gestures at an attempt to break these masculinist cycles of violence through an excursion into the simulacral.